La imagen de Monseñor Labaka como símbolo de identidad de los habitantes del Coca, periodo 1987 - 2018 - Unach (2019)
This Project aims to analyze the impact of Monsignor Labaka’s image as a symbol of identity of the inhabitants of Coca, period 1987 – 2018, as well as to identify and determine his influence through effective research methods. Highlighting his work to preserve culture, to be a bridge of peace between the oil companies, the indigenous and farmers and vice versa; fundamental essence that includes the recognition towards the just causes and on the part of Monseñor. Likewesi, Bishop Labaka is argued through publications and studies based on this character, as the main contributor to identify his ideology, based on love and respect for the Amazonian peoples. Referring also to authors such as Lévi –Strauss, Marvin Harris, Edward Tylor y Malinowski, who argue to anthropological cultural and structuralist theory, to describe their socially learned traditions, of a certain society. Regarding the applied methodology the inductive – deductive, documentary and field methods helped to verify and analyze the causes and effects of the proposed variables. The study of the research is aimed at the inhabitants of the urban area of the city of Coca, where interviews and surveys were applied to collect information and obtain results. Concluding that the image of Bishop Labaka represent the beginning of the creation of new policies by the State in defense of the Amazonian peoples. Finally, a poster was elaborated in which Alejandro Labaka’s actions are chronologically detailed